Web-Based Decision Support System for Determining the Best Employee Using the Simple Additive Weighting Method: Sistem Pendukung Keputusan Berbasis Web untuk Penentuan Karyawan Terbaik Menggunakan Metode Simple Additive Weighting - Sorongan, Delgio Liem; Kainde, Quido C; Kumajas, Sondy C (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Employee performance assessment requires structured and transparent systems to support objective decision-making in modern organizations. Specific Background: PT. Mitra Jaya Samudera still employs manual assessment procedures, causing delays and subjective evaluation outcomes. Knowledge Gap: Existing studies seldom address decision support systems tailored to processing-division characteristics in fishery-based industries. Aims: This study develops a web-based decision support system using the Simple Additive Weighting method to determine the best employees in the Processing Division. Results: The system automates normalization, scoring, and ranking across five criteria—discipline, responsibility, productivity, cooperation, and standard operating procedure compliance. Black Box Testing shows a 100% functional success rate, while User Acceptance Testing reports 95% user satisfaction. Novelty: The system integrates division-specific criteria, interactive visualization, and a structured database architecture customized for operational workflows in fish processing environments. Implications: The system provides practical support for transparent evaluation, faster managerial decisions, and scalable implementation for broader human resource management practices. Highlights • Automated web-based system calculates employee ranking using Simple Additive Weighting. • Performance evaluation uses five structured and division-specific assessment criteria. • System achieved complete functional success and high user acceptance. Keywords Decision Support System, Simple Additive Weighting, Performance Appraisal, Web-Based System, Rapid Application Development